Acute hemorrhagic leukoencephalitis mimicking herpes simplex encephalitis: case report - Henrique Milhomem Martins; Antônio Lúcio Teixeira-Jr; Marco Aurélio Lana-Peixoto (Arquivos de Neuro-Psiquiatria)
Acute hemorrhagic leukoencephalitis (AHLE) is a more severe form of acute disseminated encephalomyelities (ADEM) characterized by a fulminant clinical course and the presence of hemorrhagic necrosis of the white matter. We report the case of a 57-year-old woman who developed delirium following a respiratory infection. Magnetic resonance imaging of the brain disclosed signal abnormalities in the frontal and temporal lobes, usually found in herpes simplex encephalitis (HSE). Gram stain, India ink and acid-fast bacilli staining were all negative in CSF as was a polymerase chain reaction (PCR) for herpes simplex virus. A diagnosis of AHLE was made and the patient was treated with IV methylprednisolone 1g/day for 5 days. Despite treatment, the patient developed several neurological sequelae compatible with the severity of her illness.